2021
DOI: 10.3390/ijms222313061
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Properties of Quinone Reductase 2 Inhibitor M-11, a 2-Mercaptobenzimidazole Derivative

Abstract: The ability of NQO2 to increase the production of free radicals under enhanced generation of quinone derivatives of catecholamines is considered to be a component of neurodegenerative disease pathogenesis. The present study aimed to investigate the neuroprotective mechanisms of original NQO2 inhibitor M-11 (2-[2-(3-oxomorpholin-4-il)-ethylthio]-5-ethoxybenzimidazole hydrochloride) in a cellular damage model using NQO2 endogenous substrate adrenochrome (125 µM) and co-substrate BNAH (100 µM). The effects of M-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 108 publications
1
8
0
Order By: Relevance
“…One of the predicted 3-hop MOA paths (“Entinostat” → “decreases activity of” → “HDAC1 gene” → “interacts with” → “Histone H4” → “gene associated with condition” → “Huntington’s disease”) are supported by the previous research [Shukla and Tekwani, 2020, Yu et al, 2009]. Primaquine is predicted to act on the NQ02 gene and the IKBKG gene to play a therapeutic role in neurodegenerative disease which is reported in [Voronin et al, 2021, Singh and Singh, 2020]. Isradipine is predicted to have a potential therapeutic effect for HD by mainly regulating the genes of the Calcium Voltage-Gated Channel (e.g., CACNA1S, CACNA1D, CACNA1C, CACNB2, CACNA2D2) which might be associated with the symptoms (e.g., chorea, depression and dementia) of HD [Yagami et al, 2012] while Amifampridine is predicted to regulate the genes of the Potassium Voltage-Gated Channel to associate with HD [Noh et al, 2019].…”
Section: Other Experiments Resultssupporting
confidence: 53%
“…One of the predicted 3-hop MOA paths (“Entinostat” → “decreases activity of” → “HDAC1 gene” → “interacts with” → “Histone H4” → “gene associated with condition” → “Huntington’s disease”) are supported by the previous research [Shukla and Tekwani, 2020, Yu et al, 2009]. Primaquine is predicted to act on the NQ02 gene and the IKBKG gene to play a therapeutic role in neurodegenerative disease which is reported in [Voronin et al, 2021, Singh and Singh, 2020]. Isradipine is predicted to have a potential therapeutic effect for HD by mainly regulating the genes of the Calcium Voltage-Gated Channel (e.g., CACNA1S, CACNA1D, CACNA1C, CACNB2, CACNA2D2) which might be associated with the symptoms (e.g., chorea, depression and dementia) of HD [Yagami et al, 2012] while Amifampridine is predicted to regulate the genes of the Potassium Voltage-Gated Channel to associate with HD [Noh et al, 2019].…”
Section: Other Experiments Resultssupporting
confidence: 53%
“…The analyses above revealed that this genetic variant may disrupt LIN28 regulations on the splicing and editing events of the two adjacent genes. One gene of them ( NQO2 ) has showed its ability in neurodegenerative pathogenesis due to its roles in the increase of free radicals production under enhanced generation of quinone derivatives of catecholamines (78). Thus, the RNA editing QTL causing the phenotype changes of this gene could be pointed out as a potential biomarker of neurodegeneration.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we found 8 genes whose inferred gr-expression in the putamen were associated with variation in regional homogeneity (p ≤ 0.005). This included NQO2, whose mutations have been linked to several neurodegenerative diseases [39][40][41] . Across all ten regions, we found a total of 51 unique genes associated with regional homogeneity and 42 unique genes associated with ALFF.…”
Section: Links Between Individual Variation In Gene Expression and Ne...mentioning
confidence: 99%